Openability of soft drinks PET packagings - Silva, Danilo Correa [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Placido da Silva, Jose Carlos [UNESP] (IOS Press, 2012)
Studies on packaging accessibility are still incipient in Brazil. Many of these packagings can represent a challenge to users, whether due to non-informative labels, tricky tabs or seals, or even those that need strength to open. This paper brings a simple test to determine the necessary torque force to open PET bottles, and to predict the amount of users that could not open it. The findings suggest that a considerable amount of users could not open it or would have some difficulties to exert the necessary force.
Keywords: design; openability; usability; soft drinks; packaging